Clinical and Renal Histology Findings and Different Responses to Induction Treatment Affecting the Long-Term Renal Outcomes of Children With ANCA-Associated Vasculitis: a Single-Center Cohort Analysis - Yang, Jing; Yang, Yuan; Xu, Yongli; Zhou, Lanqi; Zhou, Luowen; Yin, Xiaoling; Pu, Jinyun; Yang, Fengjie; Liu, Yaping; He, Yonghua; Chen, Yaxian; Yuan, Huiqing; et al. (Frontiers in Immunology, 2022)
Introduction: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is relatively rare in children. This article is aimed to analyze clinical, renal histology finding and different response to induction treatment associated with the long-term renal outcomes in children with AAV in a single center. Methods: All pediatric patients with AAV admitted to Tongji hospital from Jan. of 2002 to Jan. of 2021 were included in the study. The demographic, clinical, pathological, laboratory, treatment data, and outcomes were collected and analyzed to identify predictors associated with response to induction treatment and progression to end-stage renal disease (ESRD). Results: 48 children with AAV were included in this cohort, 81.25% of them were female, 91.7% were MPA. Kidney involvement was found in 45 patients (93.75%). The most common histopathological subtype was crescentic form in this cohort according to Berden’s classification. 34 patients (70.8%) showed eGFR<60 ml/min.1.73m2 at the time of diagnosis. Complete and partial remission were achieved in 8 patients (16.7%) and 19 patients (39.6%) respectively following 6-month induction treatment. Half of the patients eventually progressed to ESRD at a mean time of (13.04±15.83) months after diagnosis. The independent predictors of non-remission following induction treatment and progression to ESRD were baseline eGFR<60 ml/min/1.73m2 and hypertension at diagnosis. Renal survival significantly decreased over time in patients with renal sclerotic subtype or those with non-remission following induction treatment by Kaplan-Meier curve estimation. Conclusions: Our study demonstrates that female, MPA, and crescentic subtype are predominant in pediatric AAV in China. Initial renal failure (eGFR<60ml/min/1.73 m2), hypertension, sclerotic pathological subtype, and non-remission following induction treatment are predictive of long-term renal outcomes.